Forming the Creative Skills of Primary Class Students on the 4k Model - Sayliyeva Mashkura Mukhtor kizi (Euro Asian Journal Publishing, 2023)
The article discusses the issue of forming the creative skills of primary school students on the 4K model
Keywords: elementary; education; skills; creativity